2015
DOI: 10.1148/radiol.2015141614
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Quantitative and Qualitative Phase-Contrast Imaging for the ex Vivo Characterization of Human Coronary Atherosclerotic Plaques

Abstract: PC imaging allows accurate characterization of human coronary artery plaques and quantitative assessment of plaque components, thereby outperforming absorption imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…With this approach, previous studies showed an increased soft-tissue contrast, e.g. in breast specimens 13 14 15 , atherosclerotic plaques 16 17 , liver lesions 18 , murine kidneys with and without renal ischemia 19 and other soft-tissue components 20 21 .…”
mentioning
confidence: 99%
“…With this approach, previous studies showed an increased soft-tissue contrast, e.g. in breast specimens 13 14 15 , atherosclerotic plaques 16 17 , liver lesions 18 , murine kidneys with and without renal ischemia 19 and other soft-tissue components 20 21 .…”
mentioning
confidence: 99%
“…6,35 Previous studies were able to show the superior diagnostic accuracy of gb-PCCT in comparison to conventional absorption CT, for the quantitative and qualitative characterization of atherosclerotic plaques using a high-resolution synchrotron setup. 36 In contrast, gb-PCCT was performed with a conventional x-ray source in the present study. The use of a conventional x-ray source is associated with a reduced resolution as well as reduced signal-to-noise ratio.…”
Section: Discussionmentioning
confidence: 98%
“…16 However, it has been shown that critical structures of atherosclerotic plaque can be differentiated using either x-ray tubes or synchrotron radiation. 2,10,36 Furthermore, the use of a conventional x-ray tube for gb-PCCT may facilitate the widespread use of this technology due to its independence of synchrotron facilities with limited access and capacities and is also closer to potential clinical applications. Optical coherence tomography is an established, accurate imaging tool for the analysis of quantitative vessel parameters, vessel anatomy, and atherosclerotic plaque lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, X-ray phase-contrast computed tomography (PCCT) has demonstrated its great potential for soft tissues imaging. 8,9 Unlike conventional absorption-based x-ray imaging which is based on the absorption of the photons, PCCT utilizes the phase shift of Xrays passing through matter to generate tissue contrast. 10 Generally, PCCT has approximately 1000-fold greater sensitivity than the conventional x-ray imaging techniques, especially in imaging weakly absorbing objects (eg, soft tissues).…”
Section: Introductionmentioning
confidence: 99%